Pengaruh Pembelajaran Aktivitas Jasmani terhadap Peningkatan Motor Ability Mahasiswa Program Studi PGSD UNM Kampus V Parepare - Iyan Iyan (ARZUSIN, 2026)
Although physical activity–based learning has received considerable attention in prior research, studies that specifically analyze its effect on improving the motor ability of students in Primary School Teacher Education (PGSD) programs remain limited, particularly within teacher education institutions. This study aimed to analyze the effect of physical activity learning on the enhancement of motor ability among students of the PGSD Study Program at Universitas Negeri Makassar (UNM) Campus V Parepare. A quantitative approach was employed using a pre-experimental one-group pretest–posttest design, involving 30 students selected through purposive sampling. Data were collected using a motor ability test instrument covering strength, speed, agility, balance, and coordination, and were analyzed using descriptive statistics and paired-samples t-tests. The results showed that the mean pretest score of 65.42 increased to 78.96 in the posttest, with an improvement of 13.54 points. The paired-samples t-test yielded a t-value of 8.27 with a significance level (Sig.) of 0.000 < 0.05, indicating a significant effect of physical activity learning on students’ motor ability. These findings contribute to the development of physical education concepts in primary teacher education and broaden the understanding of the importance of physical activity in enhancing the motor abilities of prospective primary school teachers. The study concludes that systematically planned and structured physical activity learning plays a crucial role in improving PGSD students’ motor ability and recommends that higher education institutions optimize the implementation of physical activity–based learning within the curriculum. The implications of this research include theoretical contributions to the literature on physical education and motor ability, as well as practical implications for lecturers and institutions in designing learning activities oriented toward improving students’ motor competencies, while opening opportunities for developing innovative physical activity learning models tailored to the needs of PGSD students.